Essentials of management information systems - Laudon, Kenneth C., 1944-; Laudon, Jane P. (Jane Price); Traver, Carol Guercio (Hoboken : Pearson Education, Inc., 2024)
"Essentials of Management Information Systems, 15th edition has been thoroughly updated to cover the latest industry and technology changes that impact the course. MyLab MISTM The MyLab MIS platform provides an interactive digital environment that supports the unique strengths of the content. The goal of Essentials of Management Information Systems is to provide students and instructors with an authoritative, up-to-date, interactive, and engaging introduction to the MIS field. The MyLab MIS edition extends these features to a digital platform that emphasizes videos, animations, interactive quizzes, and student comprehension of concepts, theories, and issues. The MyLab MIS environment reflects the new learning styles of students, which are more social, interactive, and usable on digital devices such as smartphones and tablets"--
Includes bibliographical references and index.
Keywords: Management information systems